THE INTERNATIONALIZATION OF SERVICES IN THE DIGITAL ECONOMY TO MITIGATE THE IMPACT OF PANDEMIC SCENARIOS - Macedo Cortes, Jonathan (Ecoforum Journal, 2022)
The lockdown generated by COVID 19 has prompted a large number of companies to migrate their business models to digital services or platforms to continue in the market. This article analyzes the factors linked to the internationalization of service firms, due to its importance on the digital economy and as a possible strategy to mitigate negative economic-effects in pandemic scenarios. The study was structured in 3 stages, first a systematic literature review of 53 high-impact articles to know about the state of the art of the internationalization process; followed by the analysis of the results based on the literature; and a third analysis of the relationship of the identified factors integrated within an affinity diagram. The research concludes that due to the future of digital economies in the world and as a strategy to counteract the negative effects of pandemics, it is necessary to deepen the analysis and try to understand the needed factors for the internationalization of service companies in the digital environment.